2022
DOI: 10.3389/fevo.2021.761293
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Seed Ingestion in Snakes: Germination Frequency and Rate, Seedling Viability, and Implications for Dispersal in Nature

Abstract: The importance of vertebrate animals as seed dispersers (zoochory) has received increasing attention from researchers over the past 20 years, yet one category in particular, diploendozoochory, remains understudied. As the term implies, this is a two-phase seed dispersal system whereby a secondary seed predator (carnivorous vertebrate) consumes a primary seed predator or granivore (rodent and bird) with undamaged seeds in their digestive tract (mouth, cheek pouch, crop, stomach, or other organ), which are subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 75 publications
(119 reference statements)
0
1
0
Order By: Relevance
“…However, it is essential to determine the retention time of the seeds in the intestines of the animals because it is an important stage in dispersal and can influence the distance the seeds can travel through the landscape (Tsuji et al, 2011 ). Diploendozoochory by felines produced longer retention times than endozoochory, with averages ranging from 30 h to almost 60 h. Although these represent very long times for seed retention, Pedrosa et al ( 2019 ) also reported long average retention times of 70 h in seeds dispersed by wild boar ( Sus scrofa ), while for another group of vertebrates, such as snakes, their retention average is much longer since the seeds can remain between 6 and 12 days in the digestive tract (Schuett et al, 2022 ). In particular, the cougar presented very long retention times of up to 96 h, so they can effectively promote the dispersal of seeds over considerable distances (Home range: 83 ± 10.3 km 2 ) from the mother plant (Nuñez‐Perez & Miller, 2019 ; Pedrosa et al, 2019 ; Varela & Bucher, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is essential to determine the retention time of the seeds in the intestines of the animals because it is an important stage in dispersal and can influence the distance the seeds can travel through the landscape (Tsuji et al, 2011 ). Diploendozoochory by felines produced longer retention times than endozoochory, with averages ranging from 30 h to almost 60 h. Although these represent very long times for seed retention, Pedrosa et al ( 2019 ) also reported long average retention times of 70 h in seeds dispersed by wild boar ( Sus scrofa ), while for another group of vertebrates, such as snakes, their retention average is much longer since the seeds can remain between 6 and 12 days in the digestive tract (Schuett et al, 2022 ). In particular, the cougar presented very long retention times of up to 96 h, so they can effectively promote the dispersal of seeds over considerable distances (Home range: 83 ± 10.3 km 2 ) from the mother plant (Nuñez‐Perez & Miller, 2019 ; Pedrosa et al, 2019 ; Varela & Bucher, 2006 ).…”
Section: Discussionmentioning
confidence: 99%